2017
DOI: 10.1002/apj.2095
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot ethanolysis of carbohydrates to promising biofuels: 5‐ethoxymethylfurfural and ethyl levulinate

Abstract: 5-Ethoxymethylfurfural (EMF) and ethyl levulinate (EL) have been considered as the new promising biofuels. A comparative study was conducted for the direct conversion of carbohydrates into EMF and EL in different medium containing ethanol. The distribution and formation kinetics of EL, EMF, 5-hydroxymethylfurfural (HMF) and levulinic acid (LA) in pure ethanol and ethanol/organic solvent medium were compared, and the results showed that the addition of nhexane can improve the accumulation of EMF. When the volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…When using biomass sugars such as sucrose, inulin, and starch as feedstocks to produce EMF, a higher content of fructose molecules in the internal biomass sugars is positively correlated with the yield of EMF. One molecule of inulin is composed of one unit of glucose and 1-59 units of fructose, and the obtained yield of EMF is between 55% and 80% [49][50][51][52]. Furthermore, one molecule of sucrose comprises one unit of glucose and one unit of fructose, with a fructose content of 50% that is lower than inulin, and its yield of EMF is between 10% and 45% [53][54][55][56].…”
Section: Di-and Polysaccharidesmentioning
confidence: 99%
See 1 more Smart Citation
“…When using biomass sugars such as sucrose, inulin, and starch as feedstocks to produce EMF, a higher content of fructose molecules in the internal biomass sugars is positively correlated with the yield of EMF. One molecule of inulin is composed of one unit of glucose and 1-59 units of fructose, and the obtained yield of EMF is between 55% and 80% [49][50][51][52]. Furthermore, one molecule of sucrose comprises one unit of glucose and one unit of fructose, with a fructose content of 50% that is lower than inulin, and its yield of EMF is between 10% and 45% [53][54][55][56].…”
Section: Di-and Polysaccharidesmentioning
confidence: 99%
“…Furthermore, one molecule of sucrose comprises one unit of glucose and one unit of fructose, with a fructose content of 50% that is lower than inulin, and its yield of EMF is between 10% and 45% [53][54][55][56]. e hydrolysate of starch [28,50], cellobiose [50,51,56], and cellulose [51,52] is glucose, so the EMF yield of these substrates is generally low. From Scheme 2, we can know that glucose-based carbohydrates (starch, cellobiose, and cellulose) have two ways to convert glucose into EMF.…”
Section: Di-and Polysaccharidesmentioning
confidence: 99%
“…However, the equipment was seriously corroded due to the H 2 SO 4 used as the catalyst. To overcome this problem, extremely low sulphuric acid (0.1 wt.% H 2 SO 4 ) was implemented as the catalyst for the synthesis of EMF from fructose by Xu et al [42], and the EMF yield was 66% at 120°C. Although the yield was decreased, it could effectively reduce the negative impact on equipment corrosion and environment.…”
Section: Homogeneous Catalytic Systemmentioning
confidence: 99%
“…Ethanol was a common solvent for the production of EMF, but humins and other by-products were easily produced during the ethanolysis of carbohydrates [90]. When organic solvents such as n-hexane [42], DMSO [82], THF [83] and γ-valerolactone (GVL) [84] were used as cosolvents, the production of by-products could be effectively reduced and the EMF yield could be remarkably increased. Wang et al [82] used "one-pot" method for EMF conversion from fructose, it was found that adding DMSO to ethanol system could increase the selectivity of the target product (EMF).…”
Section: Single-phase Solvent Systemmentioning
confidence: 99%
“…e addition of cosolvent exhibits improvement in EMF yield as compared with the single solvent, and enhanced yield of EMF ranges from 5 to 20 percentages. Xu et al [56] explored the ethanol/n-hexane mixture solvent indicating that the introduction of n-hexane could enhance the yield of EMF to 66.3% with optimum volume ratio (ethanol : n-hexane, 6 : 4), conducted at 120°C within 180 min. With the ethanol-DMSO mixture, Li et al [57] also developed acidbase bifunctional hybrid nanosphere catalyst Lys/PW that possessed an optimal reaction activity of 76.6% EMF yield from fructose, implying that the base sites of the catalysts play an important role in increasing EMF stability.…”
Section: Heteropolyacid-based Hybrid Catalystsmentioning
confidence: 99%